Psychometric properties of the Attributions About the Causes of Poverty Scale and the Attitudes Toward the Poor Scale - Reyna, Cecilia; Reparaz, María (Actualidades en Psicología, 2014)
The aim of this study was to analyze the psychometric properties of the Attributions for Poverty Causes Scale and the Attitudes toward the Poor Scale (affective dimension) in the local context. The sample was composed by 177 college students attending two institutions of Corrientes (Argentina), aged between 18 and 49 years (M = 21.94, SD =3.39), 68.4% women. The first scale showed a three-factor structure:cultural, internal and external, which replicates the original proposal, but with a smaller number of items. The second scale showed an one-dimensional structure. Both scales showed Cronbach alpha coefficients higher than .70. The relationships between the different attributions and emotional attitudes partially overlapped with those observed in previous studies. We suggest new studies in order to obtain evidence for other properties of the scales and incorporate components that are not addressed in this research.